Detecting DNA translocation through a nanopore using a van der Waals heterojunction diode - Sihan Chen; Siyuan Huang; Jangyup Son; Edmund Han; Kenji Watanabe; Takashi Taniguchi; Pinshane Y. Huang; William P. King; Arend M. van der Zande; Rashid Bashir (Proceedings of the National Academy of Sciences, 2025)
A long-unrealized goal in solid-state nanopore sensing is to achieve out-of-plane electrical sensing and control of DNA during translocation, which is a prerequisite for base-by-base ratcheting that enables DNA sequencing in biological nanopores. Two-dimensional (2D) heterostructures, with their capability to construct out-of-plane electronics with atomic layer precision, are ideal yet unexplored candidates for use as electrical sensing membranes. Here, we demonstrate a nanopore architecture using a vertical 2D heterojunction diode consisting of p-type WSe 2 on n-type MoS 2 . This diode exhibits rectified interlayer tunneling currents modulated by ionic potential, while the heterojunction potential reciprocally rectifies ionic transport through the nanopore. We achieve concurrent detection of DNA translocation using both ionic and diode currents and demonstrate a 2.3-fold electrostatic slowing of average translocation speed. Encapsulation layers enhance chemical and mechanical stability and durability while preserving the spatial resolution of atomically sharp 2D heterointerface for sensing. These results establish a paradigm for out-of-plane electrical sensing of single biomolecules.